PostCOVID effect on endothelial function in hypertensive patients: A new research opportunity - Luis Giménez‐Miranda; Luis Beltrán‐Romero; David León‐Jimenez; Pablo Stiefel (The Journal of Clinical Hypertension, 2022)
Abstract SARS‐CoV‐2 is causing devastation both in human lives and economic resources. When the world seems to start overcoming the pandemics scourge, the threat of long‐term complications of COVID‐19 is rising. Reports show that some of these long‐term effects may contribute to the main cause of morbimortality worldwide: the vascular diseases. Given the evidence of damage in the endothelial cells due to SARS‐CoV‐2 and that endothelial dysfunction precedes the development of arteriosclerosis, the authors propose to measure endothelial function around 6–12 months after acute disease in hypertensive patients, especially if they have other cardiovascular risk factors or overt vascular disease. The methods the authors propose are cost‐effective and can be made available to any hypertension unit. These methods could be the “in vivo” assessment of endothelial function by flow mediated vasodilatation after ischemia by Laser‐Doppler flowmetry and the measurement of plasma free circulating DNA and microparticles of endothelial origin.